2014
DOI: 10.1159/000356529
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune System and Inflammation in Alzheimer's Disease: From Pathogenesis to Treatment

Abstract: Immune activation and inflammation, likely triggered by amyloid-beta (Aβ) deposition, play a remarkable role in the pathogenesis of Alzheimer's disease (AD), which is the most frequent cause of dementia in the elderly. The principal cellular elements of the brain innate immune system likely to be involved in such processes are microglia. In an attempt to search for new disease-modifying drugs, the immune system has been addressed, with the aim of removing deposition of Aβ or tau by developing vaccines and huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 64 publications
(76 reference statements)
1
47
0
2
Order By: Relevance
“…Astrocytes and microglia activate the neuronal immune system in response to pathogens such as infection and vascular pathology [125],[126]. Several studies showed that senile plaques in the brains of patients with AD and of AD transgenic mice models were surrounded by an increased number of activated microglia [127].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Astrocytes and microglia activate the neuronal immune system in response to pathogens such as infection and vascular pathology [125],[126]. Several studies showed that senile plaques in the brains of patients with AD and of AD transgenic mice models were surrounded by an increased number of activated microglia [127].…”
Section: Reviewmentioning
confidence: 99%
“…Several studies showed that senile plaques in the brains of patients with AD and of AD transgenic mice models were surrounded by an increased number of activated microglia [127]. Amyloid β also activates the neuronal immune system, and might cause a chronic inflammatory reaction that has a toxic effect on nerve cells [126]. Moreover, recent genetic studies have uncovered various genes for inflammation and immune response that seem to be associated with AD [128].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There are various data on intravascular infiltration of periodontal disease-related bacteria and its spread to target organs thus far, but its mechanism of affecting diseases is not fully understood. On the other hand, the inflammatory response has been known to play a large role in the progression of cerebrovascular disorder and dementia, conditions that often occur in the elderly [8][9][10]; however, the effect of periodontal disease is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Developing novel strategies to protect cognition in the elderly population is critical for managing the disease burden and cost of care1. The pathogenesis and progression of Alzheimer’s disease (AD) (the first cause of dementia) are associated with various inflammatory processes23. Indeed, inflammatory processes play at least some role in the pathology of AD and mild cognitive impairment (MCI)4, which represents an intermediate state between normal cognitive aging and dementia.…”
mentioning
confidence: 99%